2020
DOI: 10.3390/jof6030161
|View full text |Cite
|
Sign up to set email alerts
|

German-Wide Analysis of the Prevalence and the Propagation Factors of the Zoonotic Dermatophyte Trichophyton benhamiae

Abstract: For about 10 years, a new variant of the pathogen Trichophyton (T.) benhamiae has appeared in Germany, characterized by a previously unobserved culture phenotype with a strong yellow reverse. A few studies suggest that this new variety is now the most common zoophilic dermatophyte in Germany. The guinea pig is the main carrier. Exact prevalence measurements are not yet available. Thus, the aim of our ongoing study was to collect data on the frequency and geographic distribution of the pathogen and its phenotyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
0
19
0
7
Order By: Relevance
“…indotineae . Berlin et al [ 30 ] also reported T . interdigitale from guinea pigs and hypothesized that these strains had a human origin from the breeders.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…indotineae . Berlin et al [ 30 ] also reported T . interdigitale from guinea pigs and hypothesized that these strains had a human origin from the breeders.…”
Section: Discussionmentioning
confidence: 97%
“…2), while three strains from animals belonged to T. interdigitale; none of the animal isolates was found in T. indotineae. Berlin et al [30] also reported T. interdigitale from guinea pigs and hypothesized that these strains had a human origin from the breeders.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Nagetiere tragen den für Deutschland erst seit 2008 bekannten zoophilen Dermatophyten T . benhamiae zu etwa 50 % im Fell [ 1 ]. In der Folge werden momentan deutlich mehr Kinder und Jugendliche, jedoch auch Erwachsene mit Tinea corporis, Tinea faciei und Tinea capitis durch T .…”
Section: Zoophile Dermatophyten Auf Dem Vormarschunclassified
“…Genetically, these phenotypic variants seem to be indistinguishable [5,8,15]. In the last few decades, T. benhamiae has also become a more prevalent agent of dermatophyte infection in several European regions [16][17][18][19]. It is striking to see that human infection by T. benhamiae was barely on the radar a decade ago, while it is becoming more and more commonplace nowadays [2,18,19].…”
Section: Introductionmentioning
confidence: 99%